MANIFESTATION OF BULLYING AMONG YOUNG SCHOOL-AGE CHILDREN AND APPROACHES TO IMPROVING THE PSYCHOLOGICAL ENVIRONMENT - Gulmira Jurayevna Berdiyeva; Berdiyeva Oʻgʻiloy Ulugʻbekovna (The Conference Hub, 2025)
This thesis focuses on the problem of "bullying," violence, its origins, and ways to prevent it. Bullying has harmful and long-lasting consequences for children. Beyond its physical effects, bullying also impacts children's emotional well-being and mental health, leading to isolation, depression, helplessness, and anxiety.
Keywords: Bullying, violence, group, gender, age, ancestry, race, harassment, nationality, social media, dangerous communities, social group.